Adaptive capabilities of the cardiovascular system, taking into account regulation systems, in adolescents with juvenile idiopathic arthritis - T.O. Holovko; L.F. Bogmat; N.S. Shevchenko; V.V. Nikonova; D.A. Kashkalda; O.M. Tsiura (Zaslavsky O.Yu., 2022)
Background. Juvenile idiopathic arthritis (JIA) is the most common rheumatological disease of childhood (1 : 1,000 children), which involves many organs and systems, primarily cardiovascular, with the gradual development of chronic heart failure. As you know, when the functional capacity of the heart decreases, a cascade of reactions of the neurohumoral regulation system is triggered and, first of all, the sympathoadrenal system is activated with an increase in the catecholamine production, the development of tachycardia. Due to this, the level of brain natriuretic peptide in the blood is increased. In children, chronic heart failure is asymptomatic. Therefore, determining tolerance to physical exertion plays an important role in its diagnosis. The purpose was to determine the functional state of the cardiovascular system and the tolerance to physical exertion in adolescents with JIA, taking into account the level of catecholamine excretion in the daily urine and the level of natriuretic peptide in the blood. Materials and methods. Fifty-six patients with JIA aged 12-17 years (13.28 ± 0.38 years) were examined. The control group consisted of 46 apparently healthy peers of the corresponding age. A heart ultrasound was performed to establish the functional state of the myocardium. To study tolerance to physical exertion, a six-minute walk test was performed with calculation of Kerdo index before and after the test. The level of catecholamine excretion in the urine and the level of natriuretic peptide in the blood were studied. Results. Patients with juvenile idiopathic arthritis had early signs of right ventricular myocardial systolic dysfunction (a decrease in the right ventricular ejection fraction). At the same time, we detected a decrease in the catecholamine level and an increase in the content of natriuretic peptide, which has a neuromodulatory effect at different levels of the sympathoadrenal system. Conclusions. Activation of the sympathetic division of the autonomic nervous system (increased Kerdo index) in patients with juvenile idiopathic arthritis does not ensure the effectiveness of minimal physical exertion in a six-minute walk test.